El concepto de violencia en el delito de rebelión (Art. 472 CP): a la vez, algunas consideraciones sobre los hechos juzgados en la Causa Especial 20907/2017 del TS (proceso al procés independentista catalán) = The concept of violence in the crime of rebellion (Art. 472 Spanish Criminal Code): also, some thoughts about the case against the catalan procés for independence (Supreme Court special case 20907/2017) - Llabrés Fuster, Antoni (2019)
Submitted by Iury Batista (iurys@stj.jus.br) on 2019-07-19T18:17:42Z No. of bitstreams: 2 concepto_violencia_delito_fuster.pdf: 859572 bytes, checksum: e58e4e6c8e2ea4062bedf8cce5ce7773 (MD5) license.txt: 1239 bytes, checksum: c9b4c351324448672315a00808efb725 (MD5)